Comparison of Salivary Opiorphin in Burning Mouth Syndrome and Healthy Subjects and Its Correlation With Psychiatric Disorders - Zohreh Dalirsani; Maryam Amirchaghmaghi; Mahshid Malakuti Semnani; Mahdi Talebi; Seyed Isaac Hashemy; Mohammad Taghi Shakeri; Ava Taghizadeh (Clinical and Experimental Dental Research)
ABSTRACT Objectives Burning mouth syndrome (BMS) is a chronic disease in which the patient experiences a burning sensation in the oral mucosa without any pathological cause. Opiorphin is a pentapeptide that prevents pain and can have an antidepressant effect. The aim of this study was to evaluate salivary opiorphin concentration in BMS and healthy subjects. In addition, opiorphin concentration in BMS patients before and after psychiatric treatment was compared and the association between burning severity and psychiatric scores with salivary opiorphin concentration was examined. Materials and Methods This cross‐sectional study included 28 BMS patients and 40 healthy individuals referred to the Department of Oral and Maxillofacial Medicine, Faculty of Dentistry, Mashhad, from September 2018 to August 2019. Patients with proven disease based on clinical and psychiatric examinations were included in the study. Unstimulated salivary opiorphin levels were assessed by ELISA. Statistical analysis was performed using SPSS version 24. Results Salivary opiorphin levels were significantly higher in BMS patients (2.16 ± 0.30 ng/mL) than in healthy subjects (1.80 ± 0.36 ng/mL) (p < 0.001). Opiorphin levels in BMS patients increased insignificantly after psychiatric therapy (p = 0.212). In addition, there was no significant association between opiorphin levels and age, gender, menopause, burning severity, anxiety, and depression status. Conclusions The opiorphin concentration in saliva is higher in BMS patients than in healthy subjects. Most BMS patients also suffer from anxiety and depression.